SIFAT MEKANIS DAN PENGERASAN PRESIPITASI PADUAN Al-Zn-Mg DENGAN VARIASI KANDUNGAN Cu SELAMA AGEING PADA TEMPERATUR 120 °C [Mechanical Properties and Precipitation Hardening of Al-Zn-Mg Alloys With Variation in Cu Content] - Syakuura, Abdan; Sofyan, Bondan T; Ringer, Simon P (Jurnal Metalurgi, 2012)
MECHANICAL PROPERTIES AND PRECIPITATION HARDENING OF Al-Zn-Mg ALLOYS WITH VARIATION IN Cu CONTENT DURING AGEING AT 120 °C. Aluminium-zinc-magnesium-copper alloys have an important role in aerospace industry. A systematic investigation has been done to explore microstructural evolution in Al-Zn-Mg-Cu alloys with the variation in composition (range of concentration of Zn (= Mg concentration) is 1.7-3.0 at. % and Cu in the range of 0.4-1.6 at. %) during ageing at temperature of 120oC. An induction vacuum casting unit VTC200 was employed to prepare all Al alloys. Casting microstructures was evaluated by using optical microscopy. Hardness test was performed on the aged samples to obtain the hardness curve and to reveal the influence of Cu addition on Al-Zn-Mg alloys. SEM and EDS characterization was performed to understand the precipitation microstructure evolution. Copper addition gives a significant effect on the increasing of the hardness up to 2.5 at. % of Mg and Zn (Fig. 1). In high levels of Zn and Mg content (2.9 at. %), Cu effect was no longer significant in the alloys. The white phase precipitate indicated the presence of CuMgAl2, or CuAl2, or Al7Cu2Fe if it contains Fe (Fig 2). These phases tend to increase with the Cu addition in the alloys.